2010
DOI: 10.1111/j.1532-5415.2010.03076.x
|View full text |Cite
|
Sign up to set email alerts
|

Home‐Based Leg‐Strengthening Exercise Improves Function 1 Year After Hip Fracture: A Randomized Controlled Study

Abstract: Objectives Examine the effectiveness of a short term leg strengthening exercise program compared to attentional control on improving strength, walking abilities, and function one year after hip fracture. Design Randomized controlled pilot study. Setting Interventions occurred in patients’ homes. Participants Community-dwelling older adults (n=26) six months post hip fracture at baseline. Intervention Exercise and control participants received interventions by physical therapists twice weekly for 10 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
79
0
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 31 publications
3
79
0
9
Order By: Relevance
“…Thus, reducing strength deficits should be a high priority in rehabilitation, as the incidence of falls is higher with asymmetrical lower extremity power [7] . Some trials have suggested the benefits of exercise after hip fracture [8] , but studies have most often commenced as extended programmes after standard physical therapy has ceased, 6 to 8 wk after fracture at the earliest [9][10][11][12][13][14][15][16] . To our knowledge, only one study has evaluated the effects of early 6-wk (median of 15 d postsurgery) strength training after hip fracture as an inpatient rehabilitation programme [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, reducing strength deficits should be a high priority in rehabilitation, as the incidence of falls is higher with asymmetrical lower extremity power [7] . Some trials have suggested the benefits of exercise after hip fracture [8] , but studies have most often commenced as extended programmes after standard physical therapy has ceased, 6 to 8 wk after fracture at the earliest [9][10][11][12][13][14][15][16] . To our knowledge, only one study has evaluated the effects of early 6-wk (median of 15 d postsurgery) strength training after hip fracture as an inpatient rehabilitation programme [3] .…”
Section: Introductionmentioning
confidence: 99%
“…10 The 6MWT, as an outcome measurement, has been proposed by Gmitter et al 22 to contribute to evidence-based examinations of individuals with hip fracture and has recently become more widely used in randomized clinical trials investigating the effects of different training regimens on individuals after hip fracture surgery. [23][24][25][26] However, to the best of our knowledge, the interrater reliability of the 6MWT in individuals with hip fracture has never been investigated. This lack of information is problematic because clinicians and researchers need to know whether different raters achieve similar results when testing the same individuals.…”
Section: Introductionmentioning
confidence: 99%
“…An intensive 10 wk (2 times per wk) program of progressive resistive exercises in the home 6 mo post hip fracture discharge produced changes in gait speed compared with a control group that were maintained at the 3 mo follow-up visit [7]. Home-based walking programs in older persons living in the community have supported changes in quality of life and a shuttle stamina walk test [8].…”
Section: Introductionmentioning
confidence: 99%